The Nexus of Stock Markets Among BRICS Nations : An Empirical Analysis Pre and Post Spread of the COVID-19 Pandemic - Nagina, Razia (Indian Journal of Finance, 2022)
The present corroborations from the empirical literature on the interconnections of BRICS stock markets have been conflicted. Thus, the present paper attempted to re-examine both the long and short-run nexus among BRICS stock markets before and after the COVID-19 pandemic. The current study period was segregated into two sub-periods to compare long and short-run dynamics among BRICS stock indices pre and through the times of distress and the exorbitant volatility caused by the COVID-19 pandemic. It used daily closing values of the BRICS stock market indices from January 1, 2010 to November 30, 2019 as the pre-spread COVID-19 pandemic phase and from December 1, 2019 to April 30, 2021, the post-spread COVID-19 pandemic phase. Furthermore, this study undertook the Johansen cointegration test, vector error correction model (VECM), and the Granger causality tests to examine the long and short-term nexus of the BRICS stock indices. The study findings suggested that BRICS stock markets shared linkages in totally different manners pre- and post-spread of the COVID-19 pandemic. The study findings will benefit institutional investors, individual investors, high net worth individuals, and public investors for finalizing their investment and hedging strategies for availing the opportunities of diversifying investment risk and earning high returns due to existing relations among the BRICS stock markets.